The Best of Both Worlds: Maximising the Legitimacy of the EU's Regulation of Geoengineering Research. (March 2016) - Sargoni, Janine
Abstract : This paper suggests how the regulation of Solar RadiationManagement (SRM) field research in Europe could be designed to maximise the possibility of securing legitimacy. It argues that legitimacy is maximised when regulatory frameworks are legal, and also responsive, flexible, deliberative and inclusive. By adopting an 'incorporated' approach to assessing the risk of Solar Radiation Management (SRM) field research, the EU can import elements of 'directly deliberative polyarchy' into its otherwise orthodox constitutional regulatory approach thereby maximising legitimacy. The argument is new in so far as it juxtaposes two conceptions of procedural legitimacy – one institutional and the other functional – in the context of significant scientific uncertainty in the technocratic regulatory paradigm of the EU. The significance of the work is that it draws on these conceptions of legitimacy to advance a pragmatic model of institutional design which comprises procedures that maximise legitimacy with minimal disruption to the EU's institutional balance of powers.